Morphologic characterization of the superior cerebellar artery. A direct anatomic study - Luis Ballesteros-Acuña; Fabián Gómez-Torres; H. Yesid Estupiñán (Elsevier, 2021)
Aim: to determine the morphological features of superior cerebellar artery and its branches in a Colombian population sample. Materials and methods: Ninety-three superior cerebellar arteries from cadaveric donors were studied. In each sample, the vertebral arteries were injected with semi-synthetic resin. The biometric and morphological variables of superior cerebellar arteries were measured. Results: all samples from the superior cerebellar arteries originated from the basilar artery at a distance of 27.22 ± 3.13 mm from the vertebrobasilar junction. A symmetric origin was identified in 40 samples (43%), asymmetric in 53 (57%), unilateral duplication in 41 samples (22,1%). The superior cerebellar artery bifurcated in rostral and caudal branches, mainly in the second segment in 66 samples (47.5%). This excluding cases with duplication and agenesis of SCA. The superior cerebellar artery caliber in the anterior segment (1.46 ± 0.20 mm) was significantly larger than in the lateral segment (1.37 ± 0.18 mm) (p = 0.001) and in the cerebellum-mesencephalic segment (1.25 ± 0.22 mm) (p < 0.001). In its course, the artery contacted the trigeminal nerve in 47 samples (25.9%) and the trochlear nerve passed between the rostral and caudal branches in 92 samples (51.1%). Conclusion: this study reported the highest incidence of early SCA bifurcation (40.8%) and a detailed morphometric characterization of its cortical branches. Knowledge that benefices the diagnostic imaging, clinical and surgical approach of the SCA.